Path Goal Leadership, Knowledge Sharing dan Penggunaan Teknologi Informasi Pada Kinerja Guru dengan Mediasi Self Efficacy - Sari, Maya Puspita; Handayani, Tri; Suciningtyas, Santi; Ningsih, Diah Wuriah (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2023)
This research aims to analyze the influence of Path Goal Leadership, Knowledge Sharing and Use of Information Technology on Teacher Performance with Self Efficacy as a Mediating Variable for Teachers at SMKN 1 Pemalang. Sampling was carried out using purposive sampling so that 75 teachers were used as respondents. Path analysis has been used to analyze the data and sobel test to test mediation. The results of the path analysis show that Path Goal Leadership, Knowledge Sharing, and the use of information technology have a direct and significant influence on teacher performance. Sharing knowledge is the biggest contributing factor to teacher performance. The results of the Sobel test show that self-efficacy is able to mediate the relationship between path goal leadership, knowledge sharing and use of technology with teacher performance. The application of a leadership style based on good path goal leadership, knowledge sharing and good use of information technology with teachers' confidence in their abilities will contribute to improving teacher performance at SMKN 1 Pemalang.